Foundations in microbiology - Talaro, Kathleen P.; Chess, Barry (New York : McGraw-Hill, 2015)
is an allied health microbiology text for non-science majors with a taxonomic approach to the disease chapters. It offers an engaging and accessible writing style through the use of tools such as case studies and analogies to thoroughly explain difficult microbiology concepts. We are so excited to offer a robust learning program with student-focused learning activities, allowing the student to manage their learning while you easily manage their assessment. Detailed reports show how your assignments measure various learning objectives from the book (or input your own!), levels of Bloom's Taxonomy or other categories, and how your students are doing. The Talaro Learning program will save you time while improving your students success in this course.
The Main Themes of Microbiology -- The Chemistry of Biology -- Tools of the Laboratory: Methods of Studying Microorganisms -- A survey of Prokaryotic cells and Microorganisms -- A survey of Eucaryotic Cells and Microorganisms -- An Introduction to Viruses -- Microbial Nutrition, Ecology, and Growth -- An Introduction to Microbial Metabolism : the chemical crossroads of life -- Microbial Genetics -- Genetic Engineering: a revolution in molecular biology -- Physical and Chemical Agents for Microbial Control -- Drugs, Microbes, Host -- The Elements of Chemotherapy -- Microbe -- Human Interactions: infection and disease -- An Introduction to Host Defenses and innate immunities -- Adaptive, Specific Immunity and Immunizations -- Disorders in Immunity -- Procedures for identifying Pathogens and Diagnosing Infections -- The Gram-Positive and Gram-Negative Cocci of Medical Importance -- The Gram-Positive Bacilli of Medical Importance -- The Gram-Negative Bacilli of Medical Importance -- Miscellaneous Bacterial Agents of Disease -- The Fungi of Medical Importance -- The Parasites of Medical Importance -- Introduction to Viruses That Infect Humans: The DNA Viruses -- The RNA Viruses That Infect Humans -- Environmental Microbiology -- Applied and Industrial Microbiology.
Includes bibliographical references and index.
Keywords: Microbiology; Medical microbiology